Crystal structure of 7,15-bis(4-tert-butylphenyl)-1,9-dimethylheptazethrene - Sho Kamata (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The title compound, C50H44, 1, was synthesized as a derivative of heptazethrene bearing two methyl and two tert-butylphenyl substituents, respectively, at the 1,9- and 7,15-positions. The asymmetric unit consists of one half of the molecule, which lies about an inversion centre. Albeit remotely located, the substituents contort the heptazethrene plane. The tert-butylphenyl substituents stand approximately perpendicular to the core plane, with a dihedral angle of 79.09 (5)° between the phenalene ring system and the substituted benzene ring, and prevent direct intermolecular contacts of the heptazethrene cores.